Fairtrade and beyond: Shifting dynamics in cocoa sustainability production networks. Issue 120 (March 2021) - Krauss, Judith E.; Barrientos, Stephanie
Highlights: Fairtrade, the most popular cocoa seal in the 2000s, is losing ground. Cocoa sustainability is shifting from civil-society towards company-led arrangements. Whose voices and credibility count reflects changing power/embeddedness relations. In three cocoa cases, changing sustainability dynamics exacerbate power asymmetries. We combine global production networks, sources of justification, convention theory. Abstract: Fairtrade was the most popular sustainability standard for cocoa in the 2000s, reflecting the movement's success in building credibility. There have long been debates within the Fairtrade movement over the extent of engagement with private companies, with tensions between expanding scale of engagement versus adherence to the movement's founding principles. Amid predictions of insufficient future supply, a widening spectrum of stakeholders and standard-setters is engaging in 'cocoa sustainability' initiatives. Increasingly, private companies are relying on sustainability programmes they have devised themselves, often eschewing independent certification from Fairtrade and other standard-setters. This paper asks to what extent do the changing dynamics in cocoa sustainability between civil-society standards and corporate-led initiatives exemplify larger shifts away from civil-society sources of credibility, and how is this affecting the trajectory of cocoa sustainability standards, particularly Fairtrade? Conceptually, the paper draws on global production network analysis to explore embeddedness and power asymmetries, complemented by an analysis of credibility through convention theory and sources of justification. Empirically, it reviews the changing dynamics in cocoa sustainability in terms of independent sustainability standards and major chocolate company-led programmes. It argues that the increasing reliance on corporate-led cocoa sustainability initiatives constitutes a significant shift in terms of sources of credibility, which risks exacerbating power and embeddedness asymmetries. It remains open whether this will enhance or undermine sustainability in future.